Factors Affecting Inter-Regional Human Development Index in Jambi Province - Choirur Rohmah; Suratno Suratno; Kuswanto Kuswanto; Ervan Johan Wicaksana (Jurnal Ekonomi Pembangunan, 2021)
This study aims to analyze the factors that affect the human development index between regions of Jambi Province for the 2010-2020 period. The measured factors are health, education, and economy. Health factors are measured by life expectancy. The education factor has proxy the length of school expectation and average length of schooling. The economy can be measured by expenditure per capita. The type of data in this study is secondary data, namely data obtained and collected indirectly from the object under study. The objects of this research are 9 districts and 2 cities in Jambi Province for the period 2010-2020 from the official portal of the Central Statistics Agency (BPS) Jambi Province. Data analysis through panel data regression. The finding of this study shows that life expectancy, length of school expectation, and expenditure per capita has positive effect on HDI among regions in Jambi Province. The findings can be used as material for consideration to identify various obstacles/problems faced by a particular area that has a high or low human index. After that, the government can make policies to increase one or more human development index factors that show a decline.